Creationism and the conflict over evolution - Wiley, Tatha (Cambridge : James Clark & Co., 2009)
How do our current notions of the workings of the universe fit with our deepest convictions about its meaning and value? From religion, we grasp the world as created, given, gift. From science, we apprehend it as evolving, in process, changing. How do we bring these apprehensions together? Or can we? Is our impulse to find the two complementary: creation and evolution? Or is it to find them contradictory: creation or evolution? From the Preface: The way in which we answer these questions carries personal and intellectual consequences. It will constitute the first piece in a worldview within wh.
The Bible and creation -- The meaning of creation -- Method, truth, and evolutionary science -- Catholics and the theory of evolution -- Creationism in the public arena -- Fundamentalist anxiety.
Includes bibliographical references (pages 147-154).
Description based on print version record.
Master record variable field(s) change: 072
Keywords: Creationism; Evolution -- Religious aspects -- Christianity; Religion and science; Creationism; Evolution -- Religious aspects -- Christianity; Religion and science; RELIGION / Christian Theology / General; Creationism; Evolution -- Religious aspects -- Christianity; Religion and science; RELIGION / Philosophy; Electronic books